Attitudinal and Behavioral Loyalty and Impulse Buying: Mediated Moderation of Fan-Co Creation and Satisfaction - Altaf Akbar; Hamid Riaz; Sayed Majad Koorimannil (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: Integrating social identity theory, the study aims to investigate IKEA brand customers in Portugal, focusing on attitudinal loyalty, behavioral loyalty on impulse buying, the mediating role of fan co-creation, the moderating role of fan satisfaction, and the social identity theory involved. Methodology: The study followed a quantitative and descriptive approach, utilizing primary data collected from 320 IKEA brand customers in Portugal who were actively engaged during the new design development and creation process. The research design of this study adopted a cross-sectional design, as data was collected at a single point in time. The population is unknown; a non-probability sampling technique, specifically the convenience method, was employed to select participants. After gathering the data for data analysis, Smart PLS was employed for data analysis, a technique well-suited for structural equation modeling. Findings: The results showed that attitudinal loyalty and behavioral loyalty has a significant impact on impulse buying. Furthermore, the study reveals the mediating effect of fan co-creation between attitudinal loyalty, behavioral loyalty, and impulse buying, in addition to the moderating effect of fan satisfaction on fan co-creation and impulse buying. Implications/Novel Contribution: The study enriches the theoretical framework, providing a deeper understanding of the mechanisms shaping consumer loyalty and co-creation behaviors. While offering valuable insights, the study acknowledges its limitations and suggests avenues for future research to enhance the generalizability and depth of the findings. Overall, this research contributes to understanding consumer behavior and offers practical implications for businesses aiming to cultivate brand loyalty, encourage co creation, and capitalize on impulse buying behaviors among their customer base.